Study of Urea Based Selective Non-Catalytic Reduction of NOx in Small Scale Comburtion - Khandoker, Abul Hossain (2004)
Selective Non-Catalytic Reduction (SNCR) of nitric oxide was studied experimentally by injecting different concentrations of aqueous urea solution in a pilot-scale diesel fired tunnel furnace at 3-4 % excess oxygen level and with low ppm of baseline NOx ranged from 65 to 75 ppm within the investigated temperature range. The furnace simulated small-scale combustion systems such as low capacity boilers, hot water heaters, oil heaters, etc., where the operating temperatures are usually in the range of about 973 to 1323 K and NOx emission level remains below 100 ppm. In order to investigate the influence of additive on reduction characteristics, different concentrations of commercial grade sodium carbonate (Na2CO3) were added to urea solution. The significant aspects of the studies are that it employed commercial grade urea as NOx reducing agent and commercial grade Na2CO3 as additive to urea solution to minimize the cost of the SNCR operation. NOx reductions were studied with the variation of different parameters such as injection temperature, residence time, Normalized Stoichiometric Ratio (NSR) of the reagent, carrier gas pressure, etc. A significant amount of NOx reduction was achieved which was not pronounced by the previous researchers with urea SNCR for this low ppm of NOx. With 5% plain urea solution, at an NSR of 4 as much as 54% reduction was achieved at 1128 K, whilst in the additive case the NOx reduction was improved to as much as 69% at 1093 K. Apart from this improvement, in the additive case, the effective temperature window as well as peak temperature of NOx reduction shifted towards lower temperatures. The ammonia slip measurements showed that in both cases the slip was below 16 ppm at NSR of 3 and optimum temperature of NOx reduction. Finally, the investigations demonstrated that urea based SNCR is quite applicable to small-scale combustion applications and commercial grade urea and sodium carbonate are potential NOx reducing agent and additive respectively.